Adenosine kinase deficiency: expanding the clinical spectrum and evaluating therapeutic options - Staufner, Christian; Lindner, Martin; Straub, Beate Katharina; Kölker, Stefan; Haas, Dorothea; Hoffmann, Georg F. (Journal of inherited metabolic disease, 2016)
Background Adenosine kinase deficiency is a recently described defect affecting methionine metabolism with a severe clinical phenotype comprising mainly neurological and hepatic impairment and dysmorphism. Methods Clinical data of 11 additional patients from eight families with adenosine kinase deficiency were gathered through a retrospective questionnaire. Two liver biopsies of one patient were systematically evaluated. Results The main clinical symptoms are mild to severe liver dysfunction with neonatal onset, muscular hypotonia, global developmental retardation and dysmorphism (especially frontal bossing). Hepatic involvement is not a constant finding. Most patients have epilepsy and recurrent hypoglycemia due to hyperinsulinism. Major biochemical findings are intermittent hypermethioninemia, increased S-adenosylmethionine and S-adenosylhomocysteine in plasma and increased adenosine in urine. S-adenosylmethionine and S-adenosylhomocysteine are the most reliable biochemical markers. The major histological finding was pronounced microvesicular hepatic steatosis. Therapeutic trials with a methionine restricted diet indicate a potential beneficial effect on biochemical and clinical parameters in four patients and hyperinsulinism was responsive to diazoxide in two patients. Conclusion Adenosine kinase deficiency is a severe inborn error at the cross-road of methionine and adenosine metabolism that mainly causes dysmorphism, brain and liver symptoms, but also recurrent hypoglycemia. The clinical phenotype varies from an exclusively neurological to a multi-organ manifestation. Methionine-restricted diet should be considered as a therapeutic option.
Published online: 7 December 2015
Gesehen am 13.05.2020